Factionalisation in the Prosperous Justice Party (Partai Keadilan Sejahtera): Underlying Reasons for the Emergence of the New Direction of the Indonesia Movement (Garbi) - Siregar, Sarah; Noor, Firman; Romli, Lili; Priohutomo, Hardianto (Al-Jami'ah Research Centre, 2024)
This article examines the emergence of the New Direction of Indonesia Movement (Garbi) as a result of factionalisation within the Prosperous Justice Party (Partai Keadilan Sejahtera, PKS). This study argues that a number of interconnected factors contributed to the emergence of Garbi, implying that factionalisation in political parties requires multifactor analysis rather than a single factor. This study employs qualitative data gathered through in-depth interviews with central figures in PKS and Garbi. Secondary data is gathered by analysing and reviewing scholarly sources. The study finds two factors for the emergence of Garbi: disagreements over ideological interpretation and uncompromising leadership practices. However, the findings of this study contradict a third factor, which is the absence of an effective conflict resolution process. PKS, as a cadre party, has a regeneration mechanism for dispute resolution, yet it serves as a conduit for the spread of factionalisation until the emergence of Garbi. [Artikel ini mengkaji kemunculan kelompok Gerakan Arah Baru Indonesia (Garbi) sebagai akibat dari faksionalisasi di dalam Partai Keadilan Sejahtera (PKS). Penelitian ini berargumen bahwa sejumlah faktor yang saling berhubungan berkontribusi pada kemunculan Garbi, menyiratkan bahwa faksionalisasi dalam partai politik membutuhkan analisis multifaktor daripada faktor tunggal. Penelitian ini menggunakan data kualitatif yang dikumpulkan melalui wawancara mendalam dengan tokoh-tokoh sentral di PKS dan Garbi. Data sekunder dikumpulkan dengan menganalisis dan mengkaji sumber-sumber ilmiah. Studi ini menemukan dua faktor kemunculan Garbi: ketidaksepakatan atas interpretasi ideologis dan praktik kepemimpinan yang tidak kenal kompromi. Namun, temuan penelitian ini bertentangan dengan faktor ketiga, yaitu tidak adanya proses resolusi konflik yang efektif. PKS, sebagai partai kader, memiliki mekanisme kaderisasi untuk penyelesaian konflik, namun mekanisme ini justru menjadi saluran penyebaran faksionalisasi hingga kemunculan Garbi.]